Mechanism and application of oxygen-independent photocleavage of blebbistatin as a blue or near-infrared light-gated hydroxyl radical photocage - Li, Ming-De (2020)
Development of versatile, chemically tunable photocages for photoactivated chemotherapy (PACT) represents an excellent opportunity to address the technical drawbacks of conventional photodynamic therapy (PDT) whose oxygen-dependent nature renders it inadequate in certain therapy contexts such as hypoxic tumors. As an alternative to PDT, oxygen free mechanisms to generate cytotoxic reactive oxygen species (ROS) by visible light cleavable photocages are in demand. Here, we report the detailed mechanisms by which the small molecule blebbistatin acts as a one-photon blue light-gated or two-photon nearinfrared light-gated photocage to directly release a hydroxyl radical (•OH) in the absence of oxygen.